Micromechanical framework for a 3D solid cohesion model –implementation, validation and perspectives - Sanayei, Mohammad; Farhat, Abbas; Luu, Li Hua; Werner, Lukas; Rettinger, Christoph; Philippe, Pierre; Cuéllar, Pablo (particles2021, 2021)
This article presents a solid cohesion model for the simulation of bonded granular assemblies in the frame of 3D discrete element approaches (DEM). A simple viscoplastic cohesion model for 2D geometries is extended to 3D conditions, while its yield criterion is generalized as a hyper-surface in the space of bond solicitations to include torsional moments. The model is then calibrated using experimental results of uniaxial traction at both the microscopic and macroscopic scales with an artificial granular cohesive soil. The paper finally presents some simulated results on the macromechanical sample traction application and briefly discusses the model's current limitations and promising prospects for subsequent works.
CRIS-Team Scopus Importer:2024-12-16
Keywords: DEM; Granular Cohesive Materials; Macromechanical Sample Strength; Micromechanical Tensile Failure